Preparation of monocarbonyl ruthenium complexes bearing bidentate nitrogen and phosphine ligands and their catalytic activity in carbonyl compound reduction. Issue 33 (1st August 2019) - Giboulot, Steven; Comuzzi, Clara; Del Zotto, Alessandro; Figliolia, Rosario; Lippe, Giovanna; Lovison, Denise; Strazzolini, Paolo; Susmel, Sabina; Zangrando, Ennio; Zuccaccia, Daniele; Baldino, Salvatore; Ballico, Maurizio; et al.
Abstract : A series of novel monocarbonyl ruthenium catalysts containing bidentate dinitrogen or/and diphosphine ligands are easily obtained through a general and straightforward approach. Abstract : Monocarbonyl complexes [RuCl2 (CO)(PR3 )(NN)] (R = Cy, NN = en1, ampy2 ; R = iPr; NN = en3 ) have been prepared in a one pot reaction from [RuCl2 (CO)(dmf)(PPh3 )2 ], PR3 and the NN ligand in CH2 Cl2 . Treatment of [Ru(OAc)2 (CO)(PPh3 )2 ] with NN ligands in methanol gives the cationic derivatives [Ru(OAc)(CO)(PPh3 )(NN)]OAc (NN = en4, ampy5 ) in which one acetate acts as a bidentate ligand, whereas the other is not coordinated. Diphosphine complexes [RuCl2 (CO)(PP)(PPh3 )] (PP = dppb6, dppf7, ( R )-BINAP8, ( R, S p )-Josiphos9 and ( R, R )-Skewphos10 ) have been obtained starting from [RuCl2 (CO)(dmf)(PPh3 )2 ] and the PP ligand in CHCl3 or toluene at reflux. The reaction of [Ru(OAc)2 (CO)(PPh3 )2 ] with PP in CH2 Cl2 or toluene affords the fluxional acetate derivatives [Ru(OAc)2 (CO)(PP)] (PP = dppb11, dppf12, ( R )-BINAP13, and ( R, R )-Skewphos14 ). The cationic diphosphine complexes [RuCl(CO)(PP)(en)]Cl (PP = dppb15, dppf16 ) are prepared from [RuCl2 (CO)(dmf)(PPh3 )2 ], PP and en in CH2 Cl2 or, alternatively, from [RuCl2 (CO)2 ] n or the6, 7 derivatives. Similarly, [Ru(OAc)(CO)(PP)(NN)]OAc (PP = dppb, NN = en17, ampy18 ; PP = dppf, NN = en19, ampy20 ) are isolated starting from [Ru(OAc)2 (CO)(PPh3 )2 ], PP and NN ligands or from11, 12 . The derivatives [Ru(OAc)2 (CO)(PP)] show a fluxional behavior in solution as the result of the flexible coordination of acetate ligands. These complexes are found to be active in the transfer hydrogenation and hydrogenation of ketones and aldehydes, including furfural derivatives, at an S/C up to 10 000 and a TOF up to 18 000 h −1 .